Central Versus Peripheral Artery Stiffening and Cardiovascular Risk - Yu, Shikai; McEniery, Carmel M (Arteriosclerosis, thrombosis, and vascular biology, 2020)
The large elastic arteries fulfill an important role in buffering the cyclical changes in blood pressure, which result from intermittent ventricular ejection. With aging and accrual of cardiovascular risk factors, the elastic arteries stiffen, and this process holds a number of deleterious consequences for the cardiovascular system and major organs. Indeed, arterial stiffness is now recognized as an important, independent determinant of cardiovascular disease risk. Additional, important information concerning the mechanisms underlying arterial stiffening has come from longitudinal studies of arterial stiffness. More recently, attention has focused on the role of peripheral, muscular arteries in cardiovascular disease risk prediction and, in particular, the clinical consequences of reversal of the normal gradient of arterial stiffness between central and peripheral arteries, with aging and disease.